Sensorics Board 2: Type 3840 - Technical Description - Hps SystemTechnik
With the Sensorics board a great number of experiments can be carried out in the fields of sensor and automation technology. The sensorics board compriess the folllowing main componets: 1. Segment disk: The segment disk server for examining the dynamic switching behaviour or various sensors. 2. Carriage: The carriage for taking the sensors. It can be moved either electrically or manually. 3. Electronic counter / Frequency Meter: A switchable electronic counter/frequency meter with digital display is used for pulse counting or frequency measuring. 4. Supply and Indication field: The supply and indication supplies the sensors with a standard volltage of 24 V DC anf indicates thier switching states. 5. Material sample holder: The material sample holder is used for plugging in various material samples.